Rapid partial regeneration of brain volume during the first 14 days of abstinence from alcohol - Eijk, Julia Maria van; Demirakça, Traute; Frischknecht, Ulrich; Hermann, Derik; Mann, Karl; Ende, Gabriele (Alcoholism, 2013)
Background Chronic alcohol abuse leads to severe damage of the nervous system, including a change in cerebral metabolism and brain morphology. Global volume reductions of gray matter (GM) and white matter and an increase in cerebrospinal fluid (CSF) occur after severe alcohol consumption, but abstinent alcoholics also demonstrate a brain volume recovery. The aim of this study was to investigate whether volumetric amelioration takes place already within the first 2 weeks of abstinence. Methods All 49 alcohol-dependent patients included in this study were scanned within the first 24 hours of detoxification and after 2 weeks of supervised abstinence. Amelioration of volumetric brain loss in alcohol-dependent patients has been investigated, and brain volumes have been compared with 55 healthy control subjects using whole-brain segmentation and a voxel-based morphometric approach. Results On the first day of abstinence, the global CSF volume was larger and the GM volume was smaller in alcohol-dependent patients compared with healthy controls. The largest clusters with significant volumetric differences were in the cingulate gyrus, precentral and middle frontal gyrus, cerebellum, and insula. Already after 2 weeks of abstinence, a significant albeit partial recovery of GM volume occurred in several brain regions. Conclusions Our results show that recovery of GM volume in alcohol-dependent patients starts within a few days after detoxification but varies between brain regions. This suggests that the general ability to recover and the rate as well as onset of the recovery diverges for different brain regions.